Video games ba sabi mo? a study on how people socially understand video gaming addictum. - Pormon, Vhone Houston M.
Video gaming addiction is starting to be a serious issue worldwide. In this study Social representation theory was used as a theoretical lens in investigating this phenomenon. Parents, school teachers, and students who claimed to be hooked on video games were valuable sources of data during focus group discussions. Participants associated video gaming addiction with drug addiction and likened video gamers to zombies. Video gaming addiction with drug addiction was seen as caused by being influenced by their peers and accessibility of computer shops. Being hooked on video game was seen as causing several complications to gamer?s health and they were seen as becoming more aggressive. Video gaming addiction also leads to some monetary problems and deterioration of the students? performance in school. Findings of the study point that the utility of Social Representation Theory in surfacing group knowledge about video gaming addiction as a social problem. Results also point to the need for creation and implementation of interventions and policies as well as stronger advocacy to address the problem of video gaming addiction, particularly among the youth.